Retrospective Gauging of Survival Rate and Clinical and Radiological Changes Following Regenerative Periodontal Therapy in Endodontic-Periodontal Lesions - Sneha Suresh; Sandeep Kashyap; Treena Kabiraj; Kumar Abhishek; Rosy Kumari; Leena Hari (Journal of Pharmacy and Bioallied Sciences)
Background: Endodontic-periodontal lesions present an open wound that might need surgical management using the GTR (guided tissue regeneration) to be managed using a combined approach. Aim: To assess the survival rate and clinical and radiological changes following regenerative periodontal therapy in endodontic-periodontal lesions. Methods: The study assessed 104 cases in 82 subjects with a minimum 2-year follow-up. Following scaling and root planning with/without endodontic management, regenerative procedures using DBBM with 10% collagen (Group I) or DBBM with collagen membrane (Group II) were done. radiographic bone gain, mobility, relative clinical attachment levels, gingival recession, probing pocket depth, bleeding on probing, and plaque index changes were assessed. Results: In both groups, radiographic bone gains and improved clinical parameters were seen. Greater, but statistically nonsignificant probing depth reduction was seen in the DBBM + 10% collagen group compared to the DBBM + collagen membrane group with 4.54 ± 1.04 mm and 4.06 ± 0.80 mm respectively. Comparable radiographic bone gain was seen in Groups I and II with 5.13 ± 1.52 mm and 5.33 ± 1.82 mm. A 92.33% 5-year survival rate was reported following the regenerative surgery. Conclusions: Improved radiographic bone and clinical attachment levels are seen following regenerative procedures with DBBM with 10% collagen in endodontic-periodontal lesions. Strict supportive periodontal therapy and oral hygiene can help maintain the successful results of regenerative medicine.